Synthesis of cephalosporin derivatives utilizing the cephem triflate .1. introduction of 3-position substituents via a cycloaddition-fragmentation route - Kang, HY; Lee, SH; Choi, KI; Koh, HY (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
An efficient synthetic route for cephalosporin derivatives with various substituents at the 3-position has been developed It involves cycloaddition with silyl enol ethers or silylketene acetals followed by fragmentation utilizing the 3-cephem triflate 1 as a starting material. Copyright (C) 1996 Elsevier Science Ltd